Relative Bioavailability of Two 5-mg Montelukast Sodium Chewable Tablets: A Single Dose, Randomized, Open-Label, 2-Period Crossover Comparison in Healthy Korean Adult Male Volunteers - Kim, H. T.; Song, Y.-K.; Lee, S. D.; Park, Y.; Kim, C.-K. (Arzneimittelforschung, 2012)
Montelukast sodium, cysteinyl leukotriene receptor 1 specific antagonist, has been marketed in Korea for the treatment of bronchial asthma and allergic rhinitis. The aim of this study was to compare the pharmacokinetics and relative bioavailability of a test and reference formulation of montelukast 5-mg chewable tablets in healthy Korean male volunteers to meet KFDA regulatory criteria for marketing of the new generic formulation. This study was designed as a single-dose, 2-treatment, and 2-period crossover trial with 32 healthy volunteers. Each subject was randomly assigned to receive the test (Dong-Kook Montelukast Sodium Chewable Tablet 5 mg®) or reference (Singulair Chewable Tablet 5 mg®) formulation. The tablet was chewed 20 times, and then swallowed with 240 mL of water. Plasma concentrations of montelukast up to 24 h after the dose were determined using a validated UPLC-MS/MS method, and the bioequivalence between the 2 formulations was assessed by statistical analysis of mean ratios of log-transformed AUC0–24 h and Cmax. No period or sequence effects were detected. The AUC0–24 h was 1 835 ng·h/mL for the test formulation, and 1 930 ng·h/mL for the reference formulation. The respective values of AUC0–∞ were 1 917 and 2 015 ng·h/mL. The Cmax of the test and reference products (247 and 283 ng/mL, respectively) reached at 2.25 and 2.72 h, respectively. Then, they gradually decreased with the mean terminal t1/2 of 5.25 and 5.30 h for the test and reference products, respectively. The 90% CIs for the ratio of log-transformed AUC0–24 h and Cmax for the test and reference formulations were 0.92–0.99 and 0.83–0.91, respectively. No adverse events were reported in this study. This single dose study found that the test and reference products met the regulatory criteria for bioequivalence in these fasting healthy Korean male volunteers.
Keywords: montelukast; 5-mg; chewable tablets; Korean; bioequivalence